Impact of Cyclonic Storm “Sitrang” over the Bay of Bengal on Heavy Rain and Snow in Eastern Tibet - Xiaotao Zhao; Lunzhu Danzeng; Qu Chi; Xulin Ma; Yuting Tan; Luozhu Duodian; Ranzhen Danzeng (Atmosphere)
Rainstorms and blizzards are common extreme weather events occurring in the eastern Tibet region. Their complex dynamic and thermodynamic mechanisms present challenges for regional meteorological research and forecasting. Based on station observation data and ERA5 atmospheric reanalysis datasets, a diagnostic analysis of the heavy rain and snow event in eastern Tibet from 24 to 27 October 2022 was conducted. The results indicate that (1) the influence of the cloud systems surrounding the Bay of Bengal storm “Sitrang” was a significant factor contributing to the occurrence of this heavy rain and snow weather. (2) Sustained stability of the southern branch trough and the western Pacific subtropical high favored the establishment and maintenance of the mid-level jet stream ahead of the storm. Storm “Sitrang” transported warm and moist air to eastern Tibet through the southwest mid-level jet stream, providing favorable moisture, dynamic, and thermal conditions for the heavy rain and snow. (3) Most importantly, symmetrical instability generated by the inclined motion of the storm’s warm and moist air emerged as the decisive mechanism driving the occurrence and development of the heavy rain and snow.